The Influence of Used Good-Based Learning Media on the Value of Chracter Education and Student's Motivation to Study - Rumiris Lumban Gaol; Anton Sitepu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this study was to see the effect of used goods-based learning media on the value of character education and student motivation. Something that can give effect or result from an action so as to bring a result of an effort or action taken, in this case the effect can be seen from achieving a specific instructional goal that has been planned. The place of this research is SD Sinar Pembaharuan Hidup. The subjects of this study were 35 students of grade V SD. Based on the theoretical study and data analysis, 1) based on the test criteria, the three variables have an average value of at least 3, in this case it is categorized as good. 2) the significance test of 0.005> 0.000, this test shows the effect of used goods-based division media on the value of character education and student motivation, 3) the f-value test shows that f-count> f-table is 4.192> 3.29 and 4.757> 3,29 This statement shows the influence of learning media on the value of character education and student learning motivation.